What do we know about international students and how do we know it? - Fass-Holmes, Barry; Paniagua, Ricardo (Journal of International Students, 2026)
The present exploratory study investigated whether any reports in the education research literature have overgeneralized their characterizations of American postsecondary institutions’ international students as cash cows, academically dishonest, English deficient, or exhibiting mental health issues. The concern was that overgeneralizations could give these students a negative reputation or push them away from American institutions. Purposive samples of relevant reports found by qualitative literature searches revealed evidence of overgeneralizations. This evidence suggests that overgeneralizations, in addition to the coronavirus pandemic, could play a role in international students’ postpandemically declining enrollment numbers at American institutions. Implications for the push-pull theory of international applicants’ processes for deciding where to attend college are discussed. Practices, policies, and solutions are recommended that could deter these overgeneralizations and reduce America’s risk of becoming a reverse push factor.